Mergers and acquisitions : an energy sector case study - Bonfim, Henrique Miguel Ribeiro Guimarães (2014)
When I decided to do a thesis focused on Energy Mergers and Acquisitions, EDP’s Privatization had just been launched and E.ON was one of the potential bidders. Soon after E.ON joined the pool of bidders, discussion emerged about E.ON’s motivations for the deal. Was E.ON interested in the deal for the value creation potential of acquiring EDP or was it being pressed by Berlin to participate in the bid and help show worldwide investors that the Portuguese Privatization Program was credible and contained attractive investing opportunities? Another question that arose was if E.ON would be willing to pay a fair price for EDP or if they were just looking to the deal as good bargain from a seller (Portuguese State) in need. This thesis intends to help answering these two questions. After revising valuation and M&A literature, I focused on analyzing the energy sector and both companies’ profiles. I concluded that there was, in fact, perfect economic reasoning for E.ON bidding for EDP. EDP acquisition would allow E.ON to accomplish two major strategic goals: increase the foothold in renewables and expand its presence in fast growing emerging markets. When I finished covering the first question, E.ON had already made the bid in late 2011. This allowed analyzing a posteriori the bid and concluding that the bid price offered by E.ON was reasonably below the fair price they could have paid. Ultimately, E.ON lost the bid to China Three Gorges which proposed a higher price and more favorable payment terms. E.ON lost a good opportunity to add growth and diversification to its business portfolio.